The immunomodulatory effect of oral NaHCO3 is mediated by the splenic nerve: multivariate impact revealed by artificial neural networks - Milena Rodriguez Alvarez; Hussam Alkaissi; Aja M. Rieger; Guillem R. Esber; Manuel E. Acosta; Stacy I. Stephenson; Allison V. Maurice; Laura Melissa Rodríguez Valencia; Christopher A. Roman; Juan Marcos Alarcon (Journal of Neuroinflammation, 2024)
Abstract Stimulation of the inflammatory reflex (IR) is a promising strategy for treating systemic inflammatory disorders. Recent studies suggest oral sodium bicarbonate (NaHCO3) as a potential activator of the IR, offering a safe and cost-effective treatment approach. However, the mechanisms underlying NaHCO3-induced anti-inflammatory effects remain unclear. We investigated whether oral NaHCO3’s immunomodulatory effects are mediated by the splenic nerve. Female rats received NaHCO3 or water (H2O) for four days, and splenic immune markers were assessed using flow cytometry. NaHCO3 led to a significant increase (p < 0.05, and/or partial eta squared > 0.06) in anti-inflammatory markers, including CD11bc + CD206 + (M2-like) macrophages, CD3 + CD4 + FoxP3 + cells (Tregs), and Tregs/M1-like ratio. Conversely, proinflammatory markers, such as CD11bc + CD38 + TNFα + (M1-like) macrophages, M1-like/M2-like ratio, and SSChigh/SSClow ratio of FSChighCD11bc + cells, decreased in the spleen following NaHCO3 administration. These effects were abolished in spleen-denervated rats, suggesting the necessity of the splenic nerve in mediating NaHCO3-induced immunomodulation. Artificial neural networks accurately classified NaHCO3 and H2O treatment in sham rats but failed in spleen-denervated rats, highlighting the splenic nerve's critical role. Additionally, spleen denervation independently influenced Tregs, M2-like macrophages, Tregs/M1-like ratio, and CD11bc + CD38 + cells, indicating distinct effects from both surgery and treatment. Principal component analysis (PCA) further supported the separate effects. Our findings suggest that the splenic nerve transmits oral NaHCO3-induced immunomodulatory changes to the spleen, emphasizing NaHCO3’s potential as an IR activator with therapeutic implications for a wide spectrum of systemic inflammatory conditions. Graphical abstract